THE INFLUENCE OF FINANCIAL LITERACY, REGRET AVERSION, AND HERDING ON MUTUAL FUND INVESTMENT DECISIONS AMONG GENERATION Z - I Gusti Ayu Intan Cahyani; Luh Gede Sri Artini (CV. Adiba Aisha Amira, 2026)
The increasing number of mutual fund investors in Indonesia, predominantly consisting of Generation Z, is not necessarily accompanied by rational investment decision-making. Based on behavioral finance theory, investment decisions are influenced by cognitive, psychological, and social factors. This study aims to analyse the influence of financial literacy, regret aversion, and herding on mutual fund investment decisions among Generation Z. The study employed a quantitative approach with a causal research design. Data were collected through an online questionnaire based on a Likert scale, distributed to Generation Z individuals in Denpasar City who had invested in mutual funds for at least six months, using a convenience sampling technique. Data were analysed using multiple linear regression with the assistance of SPSS, complemented by classical assumption tests and hypothesis testing. The results indicate that financial literacy, regret aversion, and herding have a positive influence on mutual fund investment decisions among Generation Z. These findings suggest that, in addition to financial knowledge, emotional and social factors also influence the investment behaviour of Generation Z. The study concludes that enhancing financial literacy and managing behavioural biases are essential to encourage better investment decision-making.